2019
DOI: 10.1002/mus.26684
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of needle electromyography in traumatic brachial plexus injury

Abstract: Introduction In this study we aimed to determine whether needle electromyographic assessment of voluntary motor unit recruitment in traumatic brachial plexus injuries could predict spontaneous motor recovery. Methods A retrospective study was performed on patients with brachial plexus injury affecting deltoid, supraspinatus/infraspinatus, and biceps brachii. The outcome measure was strength on manual muscle testing at least 1 year after injury. Good outcome was considered strength >3/5 on the Medical Research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…EMG and NCS are recognized ancillary diagnostic tests for determining the localization and severity of nerve injuries [ 16 ], as well as for monitoring the effectiveness of treatment [ 10 ]. However, due to the need for specific devices and specialized expertise, these techniques have so far not become routine tools in bovine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…EMG and NCS are recognized ancillary diagnostic tests for determining the localization and severity of nerve injuries [ 16 ], as well as for monitoring the effectiveness of treatment [ 10 ]. However, due to the need for specific devices and specialized expertise, these techniques have so far not become routine tools in bovine clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“… 30 Patients should be considered for electrodiagnostic testing between 1 and 3 months after injury to evaluate nerve continuity and deltoid innervation. 31 Recently an electrodiagnostic parameter for the detection of axillary motor nerve injury was determined by comparing a conduction study of the contralateral limb; however, it has not been shown to be a prognostic factor in treatment outcomes. 32 On the other hand, brachial plexus injuries without or with minimal voluntary motor unit potentials at 2–4 months are suggestive of poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 32 On the other hand, brachial plexus injuries without or with minimal voluntary motor unit potentials at 2–4 months are suggestive of poor outcomes. 31 Therefore, the authors recommend electrodiagnostic testing for diagnosis confirmation after 1 month of conservative management followed by repeated electrodiagnostic testing at 2–4 months to project expected outcomes with continued conservative management versus surgical neurotization. If the patient does not show improvement on the second electrodiagnostic testing, most authors would suggest surgical intervention within six months from the date of injury.…”
Section: Discussionmentioning
confidence: 99%
“…This injury causes hyper abduction of the shoulder and widening of the humeral angle of the scapula affecting the C8 and T1 nerve roots, preventing high-speed traction lead to avulsion of C5, C6, C7, C8, and T1. This mechanism refers primarily to nerve root avulsion lesions, occurs in 70-80% of the motorcycle accidents [27], [28] [29] (Figure 2).…”
Section: Definition and Pathophysiologymentioning
confidence: 99%